Hubungan Antara Sikap dan Perilaku Mengelola Sampah Pada Mahasiswa yang Tinggal di Rumah Pondok di Kabupaten Sleman Yogyakarta - Kanza Gatand Viesyszico; Arundati Shinta; Amin Al Adib (Jurnal Psikologi, 2025)
Students who have studied environmental science should be able to manage their waste properly. However, in reality, there are still many students who litter and do not manage their waste. This study aims to empirically prove the relationship between Attitude and Waste Management Behavior among boarding house students in Sleman Regency. The population in this study was students who studied environmental science and lived in boarding houses in Sleman Regency. The sample used was 100 students. The sampling technique used was Snowball Sampling. Data collection in this study used 2 scales, namely the Waste Management Behavior Scale and the Attitude Scale. This research is a type of quantitative research. Data analysis in this research is correlation test and regression test. The correlation coefficient of Attitude towards Waste Management Behavior is 0.116. The results of this study indicate that there is no positive relationship between attitudes and waste management behavior among dormitory students in Sleman Regency.